GIÚP VỚI MN ƠI!!
Bài 1:Tìm x biết:
a)\(\sqrt{x^2-4}-\sqrt{x-2}=0\)
b)\(\frac{1}{\sqrt{x}}+\frac{1}{\sqrt{y}}=4-\sqrt{x}-\sqrt{y}\)
Bài 2: Giải phương trình:
a) \(\sqrt[2]{\frac{x-1}{4}-3}=\sqrt[2]{\frac{4x-4}{9}}-\frac{1}{3}\)
b)\(\sqrt{4x-20}+3\sqrt{\frac{x-5}{9}}-\frac{1}{3}\sqrt{9x-45}=4\)
1.a) \(\sqrt{x^2-4}-\sqrt{x-2}=0\)
\(\Leftrightarrow\sqrt{\left(x-2\right)\left(x+2\right)}-\sqrt{x-2}=0\)
\(\Leftrightarrow\sqrt{x-2}.\sqrt{x+2}-\sqrt{x-2}=0\)
\(\Leftrightarrow\sqrt{x-2}.\left(\sqrt{x+2}-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}\sqrt{x-2}=0\\\sqrt{x+2}-1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\\sqrt{x+2}=1\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x+2=1\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
Vậy x=2 hoặc x=-1